Intelligent Robotics and Applications Second International Conference, ICIRA 2009, Singapore, December 16-18, 2009, Proceedings - Xie, Ming; Xiong, Youlun; Xiong, Caihua; Hu, Zhencheng (Lecture Notes in Artificial Intelligence, 2009)
This volume constitutes the refereed proceedings of the Second International Conference on Intelligent Robotics and Applications, ICIRA 2009, held in Singapore, in December 2009. The 128 revised full papers presented were thoroughly reviewed and selected from 173 submissions. They are organized in topical sections on ubiquitous and cooperative robots in smart space; advanced control on autonomous vehicles; intelligent vehicles: perception for safe navigation; novel techniques for collaborative driver support; robot and automation in tunneling; robot mechanism and design; robot motion analysis; robot motion control; visual perception by robots; computational intelligence by robots; robot and application; and robot and investigation.